Influence of elastic modulus of intraradicular posts on the fracture load of roots restored with full crowns - Ana Maria Estivalete MARCHIONATTI; Veronica VALLI; Vinícius Felipe WANDSCHER; Carlo MONACO; Paolo BALDISSARA
Abstract Objective This study aimed to evaluate the fracture load and displacement of roots restored with posts of different elastic modulus. Material and method Thirty-six replicas of epoxy resin mixed with glass microfibers were made from an endodontically-treated human premolar root prepared to a length of 12 mm with a custom drill, leaving the apical 4 mm unprepared. Replicas were randomly restored with (n = 12): FP-LM (fiber post with low elastic modulus- 50 GPa), FP-HM (fiber post with high elastic modulus - 67 GPa) and MP (metallic post - 208 GPa), using self-curing adhesive and dual resin cement. Cores were built up with composite resin and metallic crowns were cemented in all the roots with self-adhesive resin cement with self-curing mode. Specimens were subjected to a fracture load test (45° inclination/0.5 mm/min) and displacement was registered at 100 N. Result One-way ANOVA showed that elastic modulus of the post did not affect the fracture load means (p = 0.203) (FP-LM: 237.4 ± 65.11 N; FP-HM: 236.7 ± 92.85 N; MP: 295.8 ± 108.7 N) but was statistically significant for the displacement (p < 0.00): Tukey's test showed that FP-LM displacement mean (0.81 ± 0.15 mm) was significantly higher than those for FP-HM (0.46 ± 0.26 mm; p = 0.00) and MP (0.62 ± 0.07 mm; p = 0.04). Conclusion Posts with different elastic modulus exhibit similar fracture loads, but a lower displacement is achieved when fiber posts with a high elastic modulus and metallic posts are used.